Isolation of Nano Cellulose from Rubber Wood Fibre and Fibrillation Effects on Nano Cellulose Reinforced Poly (Ethylene Oxide) - Poddar, Pradeep Kumar; Gupta, Arun; Saidatul Shima, Jamari; Rashid, Shah Samiur; Sharma, Swati; Malini, Subramaniam; Jayshree, Thraisingam (Universiti Malaysia Pahang, 2016)
Wood and plants are cellular hierarchical bio-composites produced by nature, and are essentially semicrystalline cellulose microfibrilreinforced amorphous matrices made of hemicellulose, lignin, waxes, extractive and trace elements. Cellulose acts as a structural reinforcing agent that provides mechanical strength as well as chemical stability to plants. The development of low-cost, sustainable and renewable resources is critical to meet the growing environmental concerns and energy demands; the use of rubber wood is extremely beneficial to Malaysia as it is one of the main commodities. The current study aims to extract cellulose nanofibres from rubber wood (Heveabrasiliensis) fibers via high pressure homogenisation combined with enzymatic and chemical pretreatments. In this study the application of enzymes in fiber processing has been mainly directed towards the modification of hemicelluloses and lignin while preserving the cellulosic fraction .The diameter distributions of the resulting nanofibers were dependent on the number of times of cellulose solution is passing. The extent of dispersion improved significantly with increasing when number of passes through the high pressure homogenised. Fe-SEM study showed that the diameters of the nanofibersisolated ranged from 37 to 85 nanometer(nm) and estimated length is several micrometers (µm). The nanocellulosefibres were studied further by examining with Fourier Transform Infrared Spectroscopy (FTIR). There was a disappearance of vibration peaks at 1730.28 and 1234 cm-1 from spectra of treated fibres which shows the removal of hemicellulose and lignin components respectively. XRD results showed an increase in crystalline which resulted from the removal of lignin and hemicellulose. Moreover, the isolated cellulose nanofibres were used to reinforce poly(ethylene oxide) (PEO). PEO was dissolved in isolated nanocellulose liquid suspension followed by casting. The nanocomposites were characterized by using FTIR analysis and X-Ray diffractometry.